PENGEMBANGAN BUKU DIGITAL MELALUI APLIKASI SIGIL PADA MATA KULIAH COOKIES DAN CANDYS - Anggri Sekar Sari (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2017)
The development of digital book through SIGIL application in cookies and candys lessons was motivated by the lack of the interactive learning media for students. The purposes of this study were: (1) to develop digital book through Sigil Application concerning to the understanding and processing candys subject; (2) to know the feasibility of digital book based on the expertâ€™s assessment and studentâ€™s view. This study used research and development (R&D) which was modified through ADDIE development model.TheÂ  phases of study were: 1) Analysis (needs identification & book prototype formulation), 2) Design ( digital book designing), 3)Development (digital book validation by experts, reading test and media opinion by students, analysis, and revision), 4) Implementation (digital book application for learning), and 5) Evaluation (digital book evaluation). This study was conducted up to third phase - development phases.The results of the study were: 1)Â  the development of digital book through Sigil Application concerning to the understanding and processing candys, 2) the result from the experts assessment of digital book feasibility is in average percentageÂ  95,23% . As a learning media in cookies and candys lessons, it was estimated â€œextremely feasibleâ€.However, the result of students assessment in media opinion was regarded positive as it had 91,43% in average percentage which assumed that the digital books were able to be used as cookies and candys learning media.